Flann O’Brien’s Works in Scientific Studies: the Main Directions and Stages of Study - Василюк, Єлизавета Ігорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with the analysis of the history of research by means of literary criticism the works of an outstanding Irish writer Flann O’Brien, who, along with James Joyce and Samuel Beckett, is called one of three great Irish writers of the ХХth century. The main stages and aspects of this scientific process are defined, the principal works and researches of F. O’Brien’s works are determined. The researches, devoted to the study of the connection of Flann O’Brien and James Joyce, are reviewed, and the main common aspects of James Joyce and Flann O’Brien novels are named. A special attention is given to the question of Irish Gaelic language and its place in Flann O’Brien novels and to the Irish comic tradition, its aspects and research of these aspects in Ukrainian and foreign studies. The contribution of Ukrainian science to the development of the world Flann O’Brien research is being studied. Also, the influence of the Flann O’Brien International Society on the development of Flann O’Brien research is defined. The questions, which have not got a proper attention and require the development (the author’s functions, narrative strategies, the author’s influence on the Anglo-American postmodernism of the 1960s) are outlined.